Randomized controlled trial of lactulose and lactulose with probiotic in the treatment of minimal hepatic encephalopathy in chronic liver disease - Peeyush, Denis; Pradhan, Bickram (Birat Journal of Health Sciences, 2024)
Introduction: Minimal Hepatic Encephalopathy (MHE) has impact on future clinical outcomes, such as occurrence of overt hepatic encephalopathy, quality of life and survival. Objectives: To compare lactulose and lactulose with probiotic in treatment of MHE in chronic liver disease and to determine Prevalence of minimal hepatic encephalopathy in patients with chronic liver disease. Methodology: This was stratified randomized controlled trial. A total of 62 patients with MHE were analyzed. Child-Pugh Score was used to stratify the patients into three blocks of Child-Pugh Class (CPC) i.e., CPC-A, B and C. Patient in each block were randomized into two groups (lactulose alone and lactulose with probiotic). The primary end point was to evaluate cognitive status after one month of treatment with Figure Connection Test (FCT) A and B scores in comparison to the baseline. The secondary end points were to estimate the prevalence of MHE in chronic liver disease and assess association of inflammatory markers, total leucocyte count (TLC) and MHE. Results: The prevalence of MHE was 41.33%. There was improvement in FCT A and B in 90% of patients in both the groups of CPC-A. Lactulose improved FCT A and B in 45.45% and 40% while lactulose with probiotic improved it in 54.54% and 30% in CPC-B and C respectively. Patients with higher baseline values had less improvement in FCT A and FCT B. Those who didn’t improve had higher TLC in all the groups. Conclusion: There was no difference in cognitive status between lactulose alone and lactulose with probiotic in treatment for chronic liver disease patients with MHE. High baseline FCT scores and TLC had poor recovery.